1984
DOI: 10.1093/ajcp/82.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Overdose with Fetal Demise

Abstract: A case of fetal demise and maternal recovery after acetaminophen overdose is presented, to our knowledge the first reported. Fetal liver and maternal serum concentrations indicate overdose to be the cause of fetal death. Maternal disseminated intravascular coagulation (DIC) may have been related to maternal acetaminophen-induced liver disease alone or to a combination of liver disease and the presence of a dead fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Horowitz et al comment on the normal recovery of two women who ingested "repetitive, supratherapeutic (>4 g/day) doses" of APAP [5]. Haibach et al reported on a 24-year-old at 27-28 weeks EGA who ingested 29 g of APAP over less than 24 h resulting in hepatotoxicity, fetal demise and eventual maternal recovery with NAC therapy [6]. Stokes et al reported on a 17-year-old at 21 weeks EGA who ingested 25 g of paracetamol in two doses of 10 and 15 g, 18 and 8 h before admission who developed hepatotoxicity but recovered with NAC therapy to have a normal pregnancy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Horowitz et al comment on the normal recovery of two women who ingested "repetitive, supratherapeutic (>4 g/day) doses" of APAP [5]. Haibach et al reported on a 24-year-old at 27-28 weeks EGA who ingested 29 g of APAP over less than 24 h resulting in hepatotoxicity, fetal demise and eventual maternal recovery with NAC therapy [6]. Stokes et al reported on a 17-year-old at 21 weeks EGA who ingested 25 g of paracetamol in two doses of 10 and 15 g, 18 and 8 h before admission who developed hepatotoxicity but recovered with NAC therapy to have a normal pregnancy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the potential for acetaminophen toxicity in pregnancy may cause fetal deaths. Although rare, fetal deaths due to acetaminophen toxicity may arise from the inability of NAC to cross the placenta 28,29 . In such instances, 4-MP may play an adjunctive role.…”
Section: Discussionmentioning
confidence: 99%
“…66 DIC has been reported in pregnancy as the result of acetaminophen-induced hepatic necrosis associated with overdose-induced fetal death. 540 DIC has also been reported after hepatic necrosis from acetaminophen alone. 541 Cases of fulminant hyperpyrexia induced by the cytotoxic agents bleomycin and daunorubicin have been associated with shock, coma, and the development of DIC.…”
Section: Toxinsmentioning
confidence: 94%